O controle concentrado de constitucionalidades das leis municipais: limites e posssibilidades - Martins, Francisca Jeane Pereira da Silva (2005)
This study intends to analyze the possibility of changing the current Brazilian constitutional jurisdiction system, with the purpose of permitting the municipal laws and normative acts to have their legitimacy controlled by a particular judicial action able to enforce their constitutionality. The insufficiency of the diffuse judiciary system as the main mechanism to control the constitutionality of the municipal laws is the first reason to justify the referred change, considering that the effects of such judicial pronounce is restricted to the parts involved in the litigation, leading the conflict to remain latent itsef. Although, some municipal laws full of vices cannot demand incidental constitutionality verification, simply because their contents dont’t iclude concrete circumstances of litigation. It happens often with those laws involving diffuse rights or interests. Working with bibliographical research, the present study tries to demonstrate that the Brazilian cities occupy an important place on the current structure of the Brazilian Federalism, once they became a federal entity under the Federal Constitution of 1988. Thus, assuming political autonomy, it is quite natural for the municipal legislation production to be increased. Of couse, the absence of a control about the constitutionality of those municipal laws will result on their formal validity, fading the supremacy of Federal Constitution. In order to protect the harmony of the constitutional system, it is proposed to include the municipal laws among the cases that can be object of the action able to check the constitutionality of a normative act under the Supreme Court, also permitting the municipal Mayor and the members of the city House of Representatives to take the initiative of such an action. Key words: Federal State. Autonomy of the federal entities. Treatment given to the cities on the Brazilian federalism. Supremacy of Constitution. Constitutionality judicial review. Unconstitutionality of municipal laws.